Donor motivation in the era of the COVID-19 crisis: Focusing on South Korean health diplomacy and response aid to COVID-19. (March 2023) - Kim, Youngwan; Lee, Sang-Hwan; Cho, Young Jun
COVID-19 has brought an unprecedented global economic burden. The widely held view is that, during times of economic crisis, there are reduced flows of foreign aid due to budgetary constraints. Although some countries' actions seem aligned with this perspective, others, including South Korea, have acted counter-intuitively. South Korea has implemented health-related diplomacy, initiating the Agenda for Building Resilience against COVID-19 through the Development Cooperation (ABC) program. This program provides countries with COVID-19 diagnosis kits, personal protective equipment, such as masks, and health-related capacity for building and development projects. We attempt to understand the behavior of donors in the crisis context and, thus, examine South Korea as a representative case. Using South Korean health-related diplomacy as our case study, we show that South Korea has considered both its interests and recipients' needs. Furthermore, a quantitative study with newly constructed data from the ABC program reveals that South Korea provides higher amounts of Official Development Assistance (ODA) via its ABC program to recipients with whom it enjoys close economic ties and with whom it has given higher amounts of ODA. The latter finding suggests a path-dependent act in foreign aid allocation.